Strategy for Medical Informatics Education at the University of Medicine and Pharmacy in Timisoara - Mihalas, G.I.; Lungeanu, V. (Yearbook of Medical Informatics, 1997)
Our strategy for adapting a curriculum in medical informatics for medical students is presented. After a brief overview, some specific conditions are addressed, which account for some peculiarities of the objectives of our courses and of the design of the curriculum, including its integration in the overall medical curriculum. Some efforts concerning examinations and some specific educational tools are then discussed. The paper also deals with particular features concerning medical informatics education for dentistry and pharmacy students as well as for postgraduate courses, paying special attention to the doctoral level. Finally, future perspectives of medical informatics education are discussed.The paper does not present a list of successes and achievements. We had, and still have several difficulties (not always related to financial drawbacks), which required a particular approach; the word “strategy”; in the title is also meant to cover these aspects.
Keywords: Medical Informatics; Medical Education; Curriculum; Dental Informatics; Informatics in Pharmacy